Thunderstorm-triggered asthma: what we know so far - Harun NS; Lachapelle P; Douglass J (Journal of Asthma and Allergy, 2019)
Nur-Shirin Harun,1,2 Philippe Lachapelle,3,4 Jo Douglass2,31Department of Respiratory and Sleep Medicine, The Royal Melbourne Hospital, Melbourne, VIC, 3050, Australia; 2Lung Health Research Centre, The University of Melbourne, Melbourne, VIC, 3052, Australia; 3Department of Immunology and Allergy, The Royal Melbourne Hospital, Melbourne, VIC, 3050, Australia; 4Pulmonary Division, Faculty of Medicine, Université de Sherbrooke, Sherbrooke, QC, CanadaAbstract: Thunderstorm-triggered asthma (TA) is the occurrence of acute asthma attacks immediately following a thunderstorm. Epidemics have occurred across the world during pollen season and have the capacity to rapidly inundate a health care service, resulting in potentially catastrophic outcomes for patients. TA occurs when specific meteorological and aerobiological factors combine to affect predisposed patients. Thunderstorm outflows can concentrate aeroallergens, most commonly grass pollen in TA, at ground level to release respirable allergenic particles after rupture by osmotic shock related to humidity and rainfall. Inhalation of high concentrations of these aeroallergens by sensitized individuals can induce early asthmatic responses which are followed by a late inflammatory phase. Other environmental factors such as rapid temperature change and agricultural practices contribute to the causation of TA. The most lethal TA event occurred in Melbourne, Australia, in 2016. Studies on the affected individuals found TA to be associated with allergic rhinitis, ryegrass pollen sensitization, pre-existing asthma, poor adherence to inhaled corticosteroid preventer therapy, hospital admission for asthma in the previous year and outdoor location at the time of the storm. Patients without a prior history of asthma were also affected. These factors are important in extending our understanding of the etiology of TA and associated clinical indicators as well as possible biomarkers which may aid in predicting those at risk and thus those who should be targeted in prevention campaigns. Education on the importance of recognizing asthma symptoms, adherence to asthma treatment and controlling seasonal allergic rhinitis is vital in preventing TA. Consideration of allergen immunotherapy in selected patients may also mitigate risk of future TA. Epidemic TA events are predicted to increase in frequency and severity with climate change, and identifying susceptible patients and preventing poor outcomes is a key research and public health policy priority.Keywords: asthma, thunderstorm, rhinitis, ryegrass